ART TEACHING IN BRAZIL: HISTORICAL REFLECTIONS - Macao, Tayene Elize; Raimundo Yaegashi, Solange Franci; Oliveira, Terezinha [UNESP]; Lopes, Paulo (Fundacao Univ Tocantins, 2022)
This article aims to analyze the teaching of Art in Brazilian schools in the 20th century, according to formulations by Ana Mae Barbosa. The objective is to examine the challenges and achievements made by mobilizers, artists, and teachers (art educators). For this reason, it is necessary to understand the historical and social conditions of educational policies in Art, from its implementation in the 1970s to the present day, concerning Public Education. In this reflection, we will not shy away from considering the relevance of the discipline in the formation of the expressive and critical individual. To this end, it is necessary to understand the productions in History of Education and History of Art.
Keywords: Art teaching; School; Ana Mae Barbosa; History